Integrasi Sistem Informasi Akademik dan BOT Telegram Sebagai Media Pengakesan Informasi di Universitas Mataram - Ariyan Zubaidi; Ahmad Zafrullah Mardiansyah; Wirarama Wedashwara; Andy Hidayat Jatmika (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2021)
This research aims to build a chatbot based on Telegram application that integrated with academic information system in University of Mataram. The Telegram bot is expected as an alternative and more efficient way to access the academic information system. The development used the prototyping model as method of development. The Telegram bot is built using PHP that utilized the application programming interface provided by Telegram. The developed Telegram works properly displaying the results according to the commands entered. Performance of the integrated bot was measured by microtime function, to show the access time of any command. The results are then compared with the access time of the web based version that measured using the same function. The comparation shows that the access time of Telegram bot is more efficient than the web based version.